Persepsi Peserta Didik Terhadap Aplikasi Teknologi Geospasial Pada Pembelajaran Geografi Kelas X SMAN 1 Sungai Tarab - Suci Harmelya; Syafri Anwar; Susetyo, Bigharta Bekti; Gusli Martini (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
The purpose of this study was to determine the perception of class X students at SMAN 1 Sungai Tarab towards Geospatial Technology Applications. Geospatial technology is a technology that measures, analyzes, and visualizes objects or events on earth. This research uses a qualitative descriptive approach. The selection of subjects in this study used a total random sampling method consisting of 255 class X students. The research data were collected using a semi-open questionnaire method with a google form consisting of 25 questions given the answer options yes, no, and others. The results showed that there were 68.41% of students answered yes with the Good category, on the indicator of using geospatial technology applications as learning media. There were 64.61% of students answered yes with the Good category, on the indicator of the use of geospatial technology as learning material. And there are 70.44% of students answered yes with the Good category, on the indicator of the use of geospatial applications in everyday life. From the perception of students, there are still many students who do not know and use geospatial technology applications. Based on observations made at SMAN 1 Sungai Tarab, it appears that geography teachers have not utilized this geospatial technology application-based learning media.